Timing of Gastrostomy Tube Feeding in Three‐stage Palliation of Single‐ventricle Physiology. (30th May 2015) - El‐Sayed Ahmed, Magdy M.; Alfares, Fahad A.; Hynes, Conor F.; Ramakrishnan, Karthik; Louis, Clouden; Dou, Cookie; Costello, John P.; Zurakowski, David; Jonas, Richard A.; Nath, Dilip S.
Abstract: Objective: Gastrostomy tube (G‐tube) placement during three‐stage surgical palliation of single‐ventricle cardiac physiology has been shown to improve weight gain in this population of infants who often suffer from inadequate feeding. The optimal timing of this intervention is unclear and requires further investigation. Design: A retrospective review of all patients who underwent G‐tube placement at any stage of surgical palliation of single‐ventricle physiology from January 2005 to December 2012 was performed at a single congenital cardiac surgery center. Analysis of weight gain and survival was undertaken by comparing patients who received the G‐tube either less than or greater than 90 days after the first surgical stage. Results: Fifty‐four patients were identified that met the criteria, 26 (48%) of which received the G‐tube within 90 days of stage 1, while 28 (52%) patients received the tube at greater than 90 days. Percentage of weight gain at time of discharge from stage 1 was significantly higher for group B (A: median 9.9%, interquartile range [IQR] 4.9–29.8; B: median 29.0%, IQR 16.0–44.3; P = .05). However, total hospital length of stay was decreased for the patients who received G‐tubes earlier (A: median 60 days, IQR 35–100; B: median 83, IQR 48–184) as was intensive care unit length of stay (A: median 27 days, IQR 13–69; B: median 48, IQR 16–119) by nearly half, although not statistically significant ( P = .47). Survival to time of discharge from stage 1 surgery was not significantly different between earlier tube placements vs. later (92% vs. 100%, respectively; P = .14). Multivariable analysis found inclusion of fundoplication to predict weight gain ( P = .006) at time of first discharge. Conclusion: Earlier placement of G‐tube may increase the rate of recovery from stage 1 of multistage palliative cardiac surgery for single‐ventricle physiology. Fundoplication may improve perioperative weight gain when indicated.